Transforming Financial Operations through Robotic Process Automation - Venkateshwarlu Koyeda, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of Robotic Process Automation (RPA) in the financial sector, examining its implementation, benefits, and future trajectory. The article investigates how RPA technology revolutionizes core banking operations through automated workflows, enhanced accuracy, and improved efficiency. It details the technical architecture, key application areas, and critical success factors in RPA deployment while highlighting the integration with artificial intelligence and machine learning capabilities. The article encompasses various aspects of RPA implementation, from initial technical prerequisites to best practices and performance metrics, providing insights into how financial institutions can optimize their operations through automation. The article also explores emerging trends in RPA technology, including cognitive automation and cloud-based solutions, offering a forward-looking perspective on the evolution of automated financial operations.
Keywords: Artificial Intelligence Integration; Banking Process Automation; Financial Operations Transformation; Process Optimization; Robotic Process Automation